2014
DOI: 10.3846/2029882x.2013.869415
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Analysis of Design Methods for Concrete Beams Reinforced With Fiber Reinforced Polymer Bars / Kompozitais Armuotų Betoninių Elementų Projektavimo Metodų Tikslumo Analizė

Abstract: Traditional steel reinforcement does not resist corrosion and its resources are limited; therefore, carbon, glass, aramid and basalt fibre reinforced polymer bars were developed. The composite reinforcement has a high tensile strength and resistance to electromagnetic fields. Different kinds of materials and application of various surface coatings are used in the production of the composite bars. This results in different adhesion to concrete and mechanical properties of composite bars. In comparison with stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The current study is dedicated to experimental investigation of RC beams with internal and external BFRP reinforcement. The present manuscript investigates deformation behaviour and cracking of flexural elements, i.e., the predominant parameters governing serviceability of the concrete bridges, reinforced with BFRP materials (Timinskas et al 2013). The paper reports new experimental results of 4 BFRP RC beams subjected to a 4-point loading.…”
Section: Investigation On Application Of Basalt Materials As Reinforcmentioning
confidence: 98%
“…The current study is dedicated to experimental investigation of RC beams with internal and external BFRP reinforcement. The present manuscript investigates deformation behaviour and cracking of flexural elements, i.e., the predominant parameters governing serviceability of the concrete bridges, reinforced with BFRP materials (Timinskas et al 2013). The paper reports new experimental results of 4 BFRP RC beams subjected to a 4-point loading.…”
Section: Investigation On Application Of Basalt Materials As Reinforcmentioning
confidence: 98%
“…Therefore, the deformed surface is more prominent for structural application. Recent investigations by the authors (Gribniak et al 2013;Timinskas et al 2013) have revealed that grooved surface (for instance, Schöck ComBAR) reinforcement is characterized by the high quality (strength) of the bond. It could be explained by a well-balanced shape of the surface of the bar: the shear strength of concrete in the grooves is proportional to bar surface-to-core connection strength (Fig.…”
Section: Frp Materials Properties and Types Of Manufacturingmentioning
confidence: 99%
“…Comparison of characteristic and design tensile strength and elasticity modulus of different types of reinforcement(Timinskas et al 2013) …”
mentioning
confidence: 99%
“…he search for alternative material in reinforced concrete has led to many discoveries, since steel which has been the major materials in reinforced concrete have been found to get corrode easily when exposed to weather conditions, together with its very high cost. Some of the materials that have been used in place of steel bars in concrete are Fiber Reinforced Polymers (FRP), Glass Fiber Reinforced Polymers (GFRP), (Atutis et al, 2013;Gudonis et al, 2013;Timinskas et al, 2013). Most of these materials have been found to be good but will require some modifications before it can take the place of iron steel in construction.…”
Section: Introductionmentioning
confidence: 99%